Actor value formation in Airbnb: insight from multi-source data. Issue 7 (31st May 2022) - Kim, Hyunsu; Shin, Hyejo Hailey; So, Kevin Kam Fung
Abstract : Purpose: This study aims to present a novel examination of actor value formation (AVF) in the sharing economy by uncovering its key dimensions (i.e. information seeking, personal interaction and feedback) at each stage of Airbnb consumption. Using multi-source data, how the key dimensions of AVF affect consumers' evaluative judgment capturing the key aspects of consumption experiences (i.e. communication quality, value for money and overall evaluations) was empirically tested. Design/methodology/approach: This study adopted a triangulated, multi-study approach to test and validate the hypotheses. In Study 1, the authors analyzed 586, 778 online reviews through deductive and inductive approaches to determine how three AVF dimensions could be captured and examine these dimensions' effects on consumers' evaluative judgments. In Study 2, an online survey was adopted to improve the reliability and validity of findings. Findings: This study identified positive and negative outcomes of AVF. The results also revealed which AVF dimensions significantly led to communication quality and value for money, which in turn influenced consumers' overall evaluations. The findings further provided robust support for the mediating role of value for money as a mechanism in the relationships between AVF and overall evaluations across the two studies. Originality/value: This study contributes to the literature by empirically identifying the three key dimensions of AVF in each consumption stage and subsequently testing a conceptual model using different data, research methods and analytical techniques to cross-validate the results. The authors also extended the scope of AVF by integrating both positive and negative aspects in the context of Airbnb.